Cytotoxic Effects of Co1–xMnxFe2O4 Ferrite Nanoparticles Synthesized under Non‐Hydrolytic Conditions (Bradley's Reaction) – In Vitro. Issue 35 (8th November 2016) - Zachanowicz, Emilia; Zięcina, Aleksander; Mikołajczyk, Paulina A.; Rogacki, Krzysztof; Małecka, Małgorzata; Marycz, Krzysztof; Marędziak, Monika; Poźniak, Błazej; Nowakowska, Marta; Tikhomirov, Marta; Miller, Julia; Wiglusz, Rafał J.; et al.
Abstract : Co1– x Mn x Fe2 O4 ferrite nanoparticles have been synthesized by employing a microwave‐stimulated technique under non‐hydrolytic conditions. Structural, chemical, and morphological characterizations were carried out by XRD, SEM‐EDS, and TEM techniques. The stability of the nanoparticles and their tendency to form agglomerates were investigated by dynamic light scattering, exploiting the effect of different biological environments and protein stabilization. It was shown that bovine serum albumin adsorption was dependent upon the concentration and chemical composition of the nanaoparticle, showing higher affinities with increasing Co 2+ content. The cytotoxicities of the nonsurface‐blocked Co1– x Mn x Fe2 O4 nanoparticles were assessed for three cell lines: phagocytic murine macrophage (J774.E), cancer fibroblast human osteosarcoma (HTB), and mesenchymal stem cells derived from human adipose tissue (ASCs). The results indicate that the cytotoxic response strongly depends on the particle concentration as well as the type of cell line. Abstract : The in vitro cytotoxicity of superparamagnetic Co1– x Mn x Fe2 O4 nanoparticles has been assessed for three cell lines: The murine macrophage (J774.E), human osteosarcoma (HTB), and mesenchymal stem cells (ASCs) showed responses strongly dependent upon the cell type.